INCLUSIVE EDUCATION IN ITALY - Voitkāne, Vita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
European member States implement Inclusive Education policies thus contributing to a sustainable, inclusive society, although each country is at a different stage in this process. Italy, one of the first countries to launch integrative learning, has set an example since the 1970s, although the quality of inclusive education is unpredictable due to many issues. Authors Cantoni and Panetta (2006) emphasize that, although the culture of integration in Italy exists, much needs to be done to improve the quality of inclusive education and at present new, innovative projects are exploring strategies to this effect, the results of which will lead to a national reform on Special Needs Education.The aim of this study is to learn about Italian solutions to inclusive education, the obstacles presented, results achieved and people's attitudes to inclusivity, by carrying out theoretical and empirical research using Action as Research method. A survey was carried out on pupils’ parents and educational staff, the results of which reveal a variety of existing issues around quality assurance in inclusive education. Consequently people's thoughts and attitudes towards inclusive education are divided, however the majority of people are in agreement that Inclusive education is the best solution for everyone concerned, pupils, parents and teachers. This research is in agreement with the the Salamanca Declaration (1994, IX) which states that inclusive education is an evolving process - not the end result.